Short-stay facilities in accident and emergency departments for children. Issue 3 (September 1993) - Beattie, T F; Ferguson, J; Moir, P A
Abstract : This paper assesses short stay ward facilities for children in the United Kingdom. The results of a postal questionnaire indicate that 50% of departments surveyed have a short-stay ward. Of these 25% admit small numbers of children. These are mainly children who have sustained trauma-related problems. The potential role of paediatric short-stay ward facilities is discussed.